Pengaruh Implementasi Sistem Informasi Administrasi Kependudukan (Siak) Terhadap Efisiensi Alur Pelayanan Publik Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Mamuju - Greis; Staowrina, Endang; Yeni, Hari (CV. SINAR HOWUHOWU, 2026)
ABSTRACT This research aims to empirically evaluate the influence of the Population Administration Information System (SIAK) implementation on the efficiency of public service workflows at the Population and Civil Registration Office (Disdukcapil) of Mamuju Regency. The study is prompted by the critical need to address bureaucratic inefficiencies and fluctuating service lead times through digital transformation. Adopting a quantitative approach, this study designates the quality of the SIAK system as the independent variable (X) and the efficiency of service workflows as the dependent variable (Y). The research population comprises service users in Mamuju Regency, with a sample of [Insert Number] respondents selected via simple random sampling techniques. Data collection was executed through structured questionnaires utilizing a Likert scale, previously validated for internal consistency and reliability. Data analysis was performed using descriptive statistics, classical assumption tests, and simple linear regression analysis to verify the research hypotheses. Preliminary findings suggest that the implementation of SIAK exerts a positive and significant influence on workflow efficiency. This indicates that the optimization of information system performance directly correlates with enhanced efficiency in time management, operational costs, and procedural simplification. These results provide strategic insights for Disdukcapil Mamuju to further strengthen their information technology infrastructure, thereby mitigating procedural bottlenecks and fostering a more responsive public administration environment.